Neonatal Mortality Disparities by Gestational Age in European Countries - Sartorius, Victor; Philibert, Marianne; Klungsoyr, Kari; Klimont, Jeannette; Szamotulska, Katarzyna; Drausnik, Zeljka; Velebil, Petr; Mortensen, Laust; Gissler, Mika; Fresson, Jeanne; Nijhuis, Jan; Zhang, Wei-Hong; et al. (JAMA network open, 2024)
IMPORTANCE: There are wide disparities in neonatal mortality rates (NMRs, deaths <28 days of life after live birth per 1000 live births) between countries in Europe, indicating potential for improvement. Comparing country-specific patterns of births and deaths with countries with low mortality rates can facilitate the development of effective intervention strategies. OBJECTIVE: To investigate how these disparities are associated with the distribution of gestational age (GA) and GA-specific mortality rates. DESIGN, SETTING, AND PARTICIPANTS: This was a cross-sectional study of all live births in 14 participating European countries using routine data compiled by the Euro-Peristat Network. Live births with a GA of 22 weeks or higher from 2015 to 2020 were included. Data were analyzed from May to October 2023. EXPOSURES: GA at birth. MAIN OUTCOMES AND MEASURES: The study investigated excess neonatal mortality, defined as a rate difference relative to the pooled rate in the 3 countries with the lowest NMRs (Norway, Sweden, and Finland; hereafter termed the top 3). The Kitagawa method was used to divide this excess into the proportion explained by the GA distribution of births and by GA-specific mortality rates. A sensitivity analysis was conducted among births 24 weeks' GA or greater. RESULTS: There were 35 094 neonatal deaths among 15 123 428 live births for an overall NMR of 2.32 per 1000. The pooled NMR in the top 3 was 1.44 per 1000 (1937 of 1 342 528). Excess neonatal mortality compared with the top 3 ranged from 0.17 per 1000 in the Czech Republic to 1.82 per 1000 in Romania. Excess deaths were predominantly concentrated among births less than 28 weeks' GA (57.6% overall). Full-term births represented 22.7% of the excess deaths in Belgium, 17.8% in France, 40.6% in Romania and 17.3% in the United Kingdom. Heterogeneous patterns were observed when partitioning excess mortality into the proportion associated with the GA distribution vs GA-specific mortality. For example, these proportions were 9.2% and 90.8% in France, 58.4% and 41.6% in the United Kingdom, and 92.9% and 7.1% in Austria, respectively. These associations remained stable after removing births under 24 weeks' GA in most, but not all, countries. CONCLUSIONS AND RELEVANCE: This cohort study of 14 European countries found wide NMR disparities with varying patterns by GA. This knowledge is important for developing effective strategies to reduce neonatal mortality.
Keywords: gestační stáří; ženské pohlaví; lidé; Infant, Newborn; Infant Mortality; novorozenec; narození živého dítěte; Live Birth; Gestational Age; Health Status Disparities; Humans; kojenecká mortalita; disparity zdravotního stavu; průřezové studie; Infant; Europe; mužské pohlaví; Cross-Sectional Studies; Male; kojenec; Evropa; Female